Answer :

Given that: Sn denote the sum of first n terms

and S2n = 3Sn


To find: S3n : Sn


Now, we know that




S2n = n[2a + (2n – 1)d]


As per the given condition of the question, we have


S2n = 3Sn




4an + 2nd(2n – 1) = 6an + 3nd(n – 1)


2nd(2n – 1) – 3nd(n – 1) = 6an – 4an


4n2d – 2nd – 3n2d + 3nd = 2an


nd + n2d = 2an


nd(1 + n) = 2an


d(n + 1) = 2a …(i)


Now, we have to find S3n:Sn


So,



[from (i)]





Hence, the correct option is (b)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

There are n A.M.sRD Sharma - Mathematics

If x, y, z are inRD Sharma - Mathematics

Insert 7 A.M.s beRD Sharma - Mathematics

The 10th</suRD Sharma - Mathematics

Insert five numbeRD Sharma - Mathematics

The 4th</supRD Sharma - Mathematics

Insert 4 A.M.s beRD Sharma - Mathematics

Show that x2RD Sharma - Mathematics

An A.P. consists RD Sharma - Mathematics

How many terms arRS Aggarwal - Mathematics